Persepsi Pedagang Terhadap Pelayanan Petugas Pasar Tradisional Bangil - Ishak Ishak (Fakultas Ekonomi Universitas Panca Marga, 2021)
The fokus of this research is trader’s perceptions of service quality with a focus of research in Bangil traditional market officers. The purpose of this study was to determine how much the quality of public services in Bangil tradional market unit. The method of this research is quantitative descriptive, the subjects of this study are traders rgistred as many as 1396 taders and as a population. The sampling technique used was simple random sampling using the opinion of Slovin, with a total of 93 respondents. Based on yhe result of the study showed the quality of market services is near maximum. Keywords : Perception Of Merchant, Service Quality